2003
DOI: 10.1007/s00423-003-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of proximal bile duct cancer: extended right lobe resection increases resectability and radicality

Abstract: Right trisegmentectomy and combined portal vein resection represent the best way to comply with basic rules of surgical oncology for hilar cholangiocarcinoma. This procedure will provide the most pronounced benefit among various types of liver resection, whereas local resections of the extrahepatic bile duct must be considered as an oncologically inefficient procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 22 publications
1
112
0
6
Order By: Relevance
“…Several strategies have been developed to improve outcomes. One such strategy is partial hepatic resection with concomitant en-bloc resection of vascular structures and accompanied by reconstruction along with biliary excision for complex hilar tumors (60,67). Indeed, even in patients with BismuthCorlette Stage II tumors involving the confluence of the right and left hepatic ducts, caudate lobe resection is recommended because the bile ducts from the caudate lobe drain directly into the confluence and cancer frequently extends up these ducts into the caudate lobe.…”
Section: Therapy Curative Surgical Resectionmentioning
confidence: 99%
“…Several strategies have been developed to improve outcomes. One such strategy is partial hepatic resection with concomitant en-bloc resection of vascular structures and accompanied by reconstruction along with biliary excision for complex hilar tumors (60,67). Indeed, even in patients with BismuthCorlette Stage II tumors involving the confluence of the right and left hepatic ducts, caudate lobe resection is recommended because the bile ducts from the caudate lobe drain directly into the confluence and cancer frequently extends up these ducts into the caudate lobe.…”
Section: Therapy Curative Surgical Resectionmentioning
confidence: 99%
“…It was recently reported that aggressive surgical strategies in the treatment of ICC can significantly increase the survival of ICC patients [14,80,81] . Yamamoto et al [82] and Ohashi et al [83] suggested that anatomic and extensive hepatectomy is the rational procedure for mass-forming ICC, while hepatectomy with extrahepatic duct excision, and hilar lymph nodal resection is the rational procedure for infiltrating ICC.…”
Section: Hepatectomymentioning
confidence: 99%
“…предложили новую методику достижения радикального хирургическо-го лечения перихилярной холангиокарциномы [31,32]. Это так называемая hilar en block резекция, или non-touch техника, включающая в себя расширен-ную правостороннюю трисекциоэктомию (Sg 1, 4-8), резекцию бифуркации воротной вены, резек-цию правой печеночной артерии и внепеченочных желчных протоков.…”
Section: îáñóAeäåíèåunclassified